How About The Resilience of Students Who Have Mothers as Victims of Domestic Violence? - Arnaldy Arnaldy Arnaldy; Yarmis Syukur; Herman Nirwana (Journal of Counseling, Education and Society, 2020)
The ability in the form of individual toughness to be ready to face bitter realities is known as resilience. Resilience is needed by students, one of which applies as the child of a parent of victims of domestic violence. This research is a qualitative research with a case study approach. The study was conducted at one of the High Schools in the City of Padang. The subjects in this study were one student with criteria as a child whose parents (mother) experienced domestic violence, counseling teachers and parents of students. Taking the subject of this study using purposive sampling method. This study uses data collection techniques with interviews and observations. The technique guarantees the validity of the data carried out by building close relationships with subjects and informants naturally and continually making observations. Data analysis technique is done by data reduction, data display and conclusion drawing and verification. The results revealed that the conditions of resilience of parents (mothers) of domestic violence victims are as follows: (1) IRs have immature emotional control when dealing with domestic violence experienced by their mothers, (2) IRs have poor impulse control when dealing with domestic violence experienced by their mothers , (3) IR has good optimism when facing domestic violence experienced by his mother, (4) IR is still not good at analyzing problems carefully, (5) IR has good empathy, (6) IR has good self-efficacy, and (7) IRs have good reaching out when dealing with their mothers as victims of domestic violence. So, it can be concluded that IR has a fairly good resilience.